A biorthogonal chemistry approach for high-contrast antibody imaging of lymphoma at early time points - Swarbhanu Sarkar; Jonathan M. Pham; Kimberly J. Edwards; Nitika Sharma; Kexiang Xu; A. Paden King; Andres Fernandez del Castillo; Michael D. Farwell; Daniel A. Pryma; Stephen J. Schuster; Mark A. Sellmyer (EJNMMI Research)
Abstract Background Monoclonal antibodies are highly specific for their targets making them effective for cancer therapy. However, their large molecular weight causes slow blood clearance, often requiring weeks to be removed from circulation. This limitation affects companion nuclear imaging and antibody-based diagnostics, necessitating delayed imaging. We report the expansion of a methodology improving positron emission tomography (PET) contrast of the lymphoma biomarker CD20 at early time points after radiolabeled antibody administration. Intact radioimmunoconjugates are allowed to stay in circulation long enough to accumulate in tumors, and then, using a chemical trigger, we induced rapid clearance of the radioactivity from non-target tissues by cleaving the linker between the antibody and the radioactivity. For brevity, we refer to the this as the Tetrazine KnockOut (TKO) method which uses the transcyclooctene-tetrazine (TCO-Tz) reaction, wherein an antibody is conjugated with linker containing TCO and a radioisotope. Results We optimized the TCO linker with several different radioisotopes and evaluated the ability of tetrazines to knockout radioactivity from circulating antibodies. We explored several cell types and antibodies with varying internalization rates, to characterize the parameters of TKO and tested [89Zr]Zr-DFO-TCO-rituximab in a lymphoma model with PET imaging after Tz or vehicle administration. Treatment with Tz induced > 70% cleavage of the TCO linker in vitro within 30 min. Internalizing radioimmunoconjugates exhibited similar cellular uptake with Tz compared to vehicle, whereas decreased uptake was seen with slowly internalizing antibodies. In rodents, Tz rapidly liberated the radioactivity from the antibody, cleared from the blood, and accumulated in the bladder. TKO resulted in > 50% decreased radioactivity in non-target organs following Tz injection. No decrease in tumor uptake was observed when rate of antibody internalization is higher in a lymphoma model, and the target-to-background ratio increased by > twofold in comparison with Tz nontreated groups at 24 h. Conclusion The TKO approach potentiates early imaging of rituximab radioimmunoconjugates and has translational potential for lymphoma imaging. Graphical abstract